Autisme et Douleur – Analyse Bibliographique. (2010) - Dubois, Amandine; Rattaz, Cécile; Pry, René; Baghdadli, Amaria
Abstract : The purpose of the present article was to assess the available literature concerning pain and autism. First, authors summarized the published articles on pain reactivity in people with autism. Second, the hypotheses envisaged to explain the presence of expressive particularities in people with autism spectrum disorders were reviewed; these included endogenous opioid excess theory, sensorial abnormalities and sociocommunicative deficit. Finally, the present review dealt with the tools available to assess and manage pain in people with autism. In conclusion, the authors revealed the need for more research to obtain more consensual data and provided some recommendations in this domain that were underexploited by the scientific community. From a clinical point of view, more knowledge about pain in people with autism should enable the development of specific assessment tools and, consequently, better pain management in daily care.